2006
DOI: 10.1373/clinchem.2005.048983
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mRNA in Whole Blood by Assessing Recovery of RNA and Efficiency of cDNA Synthesis

Abstract: Background: Current gene expression analysis relies on the assumption that the isolated RNA represents all species of mRNA in proportions equal to those in the original materials. No system is available for absolute quantification of mRNA. Methods: We applied whole blood to 96-well filterplates to trap leukocytes. Lysis buffer containing cocktails of specific reverse primers and known concentrations of synthetic external control RNA (RNA34) was added to filterplates, and cell lysates were transferred to oligo(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 28 publications
3
59
0
Order By: Relevance
“…The cyclin-dependent kinase inhibitor 1A (p21) mRNA was increased without any stimulation (Fig. 1B, ○◊∆) as shown in our previous studies (Mitsuhashi et al 2006). This result indicated that the values of time = 0 were not appropriate control, and vehicle control was used throughout except Figure 1A-C.…”
Section: Apoptosis Inductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The cyclin-dependent kinase inhibitor 1A (p21) mRNA was increased without any stimulation (Fig. 1B, ○◊∆) as shown in our previous studies (Mitsuhashi et al 2006). This result indicated that the values of time = 0 were not appropriate control, and vehicle control was used throughout except Figure 1A-C.…”
Section: Apoptosis Inductionsupporting
confidence: 87%
“…The Ct values of RNA34 were converted to copy number, and the % recovery was calculated in each well. For cellderived mRNA, the Ct values were converted to the copy number using respective calibration curves, and these values were further converted to copies/µl blood by dividing with % recovery of RNA34 in each sample (Mitsuhashi et al 2006). Each copy number of drug-treated triplicate samples was divided by the mean copy number of control samples (vehicle-treated ones) to calculate the mean ± standard deviation of the values of the fold increase.…”
Section: Mrna Quantifi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in Cycle threshold (C t ) between the target and control mRNA (β actin) (ΔC t ) were used to quantify the relative amount of each target, calculated as 2 ÀΔC t . Primers used for gene expression assays have been previously described [25][26][27][28].…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Previously we introduced a unique system of leukocyte mRNA analysis from whole blood, in which leukocytes were trapped on a 96-well filter plate and leukocyte lysate was transferred to a 96-well oligo(dT)-immobilized microplate for direct poly(A) ϩ mRNA purification followed by cDNA synthesis and PCR (7)(8)(9). In this study, the leukocyte-capture filter plate was replaced with the newly developed EMV-capture filter plate, and HPC-derived mRNAs were quantified in plasma.…”
mentioning
confidence: 99%